FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN: (Studi Pada Perusahaan Sektor Teknologi di Indonesia) - Indah Lia Puspita; Eka Sariningsih; Indah Yuning Tias (UNHI Press, 2026)
This study examines the effect of capital structure, dividend policy, working capital efficiency, intellectual capital, Good Corporate Governance (GCG), and growth opportunity on firm value in technology sector companies listed on the Indonesia Stock Exchange during 2022–2024. This research uses a quantitative approach with secondary data from financial and annual reports. The sample consists of 31 companies selected using purposive sampling. Data were analyzed using multiple linear regression with SPSS. The results show that capital structure, dividend policy, working capital efficiency, and Good Corporate Governance do not significantly affect firm value. In contrast, intellectual capital and growth opportunity have a positive and significant effect. These findings indicate that knowledge-based assets and growth potential are key factors in increasing firm value, especially in the technology sector.